Assets Valuation Approaches & its Reflects on Financial Reporting Quality - خضير بشرى فاضل; حميد مصطفى يونس (Journal of Economics and Administrative Sciences, 2013)
Abstract The model of financial reporting in Iraq Based on a specific set of accounting objectives & concepts, which require the application of the historical cost valuation approach due to the nature of the objectives of financial reporting in Iraq, established under the unified accounting system , which focuses on serving the needs of the state because it the most influential user in setting accounting objectives and concepts, which stems mainly from the nature of the economic system in Iraq, which focuses on the public sector versus the private sector as well as the nature of the ownership business that focuses on partnership versus corporations, as well as Preference community members about savings versus investment and recent formation of the financial market in Iraq . Because historical cost valuation approach ignores changes in assets values due to the prices fluctuations , technical progress and technological and this ignorance affect the measurement of accounting profit , which is a function of the financial reporting quality , so the quality of financial reporting of Iraq’s economic units is low, which requires reconsideration of accounting objectives and concepts and adoption alternative approaches for assets valuation (replacement cost , net realizable value and fair value) as a prelude to improve the quality of financial reporting in Iraq.